Thinking about the “new” Equality - Barboza Tello, Marco León Felipe (2025)
This article provides an explanatory and historical account of Equality, considering its constitutive bases fifty years ago, and then provides elements of a diagnostic and casuistic update, in which its current complications and difficulties on a global scale are made explicit, as well as describing the distortions in the justice system when mechanisms of undue economic influence are developed that corrupt the institutional order. It also develops a basic prospective of equality based on recent developments in international human rights jurisprudence, specifically the reports of the UN Special Rapporteurs. Finally, elements of the relationship between the “new world” of rights and emotions are noted. Concluding that, between the revaluation of the human condition and the marketing of digitized perfection, there is space to breathe, recharge our batteries, and not succumb to the frenetic pace of digitalized time so characteristic of cities, and that this needs to be recognized for its precedence and inherent dignity; and, in the not-too-distant future, to consolidate “The right to be sufficient”.